A Cross Sectional Study Evaluating Internet Addiction and Depression Levels among Medical and Engineering Students of Bengaluru City - Ipsita Debata; Sunil Kumar; Vasanth kumar; Greeva Philip (Medsci Publications, 2018)
Introduction: The study was conducted to determine the preva- lence of Internet addiction, to assess the levels of depression, an- xiety and stress among medical and engineering students and to correlate the level of internet addiction with depression levels. Methods: A cross sectional study was carried out among 200 first year undergraduate students, 100 each from medical and engineer- ing colleges of Bengaluru city, selected by simple random sam- pling method. Data was collected by interpersonal interviews us- ing a standardized 'Internet Addiction Test' questionnaire by Dr. Kimberly S. Young and 'Depression, Anxiety and Stress Scale (DASS)-21' questionnaire by Psychology foundation, UNSW, Aus- tralia. Results: In total of 200 students, the mean age of participants was 18.85 ± 0.197 years. Males constituted 52% while females consti- tuted 48% of study population. The prevalence of Internet addic- tion was 67%. Prevalence of Depression, Anxiety and Stress in the study population was 49.5%, 52.5% and 67.5% respectively be- cause of internet addiction. Statistically significant association (p=0.0002) was found between internet addiction and depression levels; between depression and anxiety levels (p=0.00001); depres- sion and stress levels (p=0.0002). Conclusion: The present study highlights the vulnerability of pro- fessional college students to internet addiction. Internet addiction also seems to be associated with increasing prevalence of depres- sion, anxiety and stress.